Social Innovation of PT. Pertamina EP Pendopo Field for Conservation the Protected Orchid Plants in Selangit Village, Musi Rawas Regency - Mohammad Nur Samudin W; Suharyadi Suharyadi; Hengky Rosadi; Renny Maulidda; Nyayu Latifah Husni; Ade Silvia Handayani; Muhammad Rezza (Asian Journal of Social and Humanities, 2023)
A rescue program was made to save orchid plants in Selangit Village by initiating and involving the community. This activity began in 2017 and now, more than 250 species of orchid plants have been successfully rescued. The decline of some species of orchid plants are due to many factors, such as the endemic nature, forest fire, illegal logging, and illegal sales by collector can be an accelerator of their extinction.  This activity can be a trigger to increase insight and ideas for the government and local community in developing natural areas. Working together between PT. Pertamina EP Pendopo Field and South Sumatera Natural Resources Conservation Center to build the Selangit Greenhouse aims to save orchid plants and can be an education facility for educators and learners. Next, this program advised to development of tourist village destinations by increasing training and promotion activities of flora tourism activities, and can be sustainable social activity in rescuing orchids and rare plants in Selangit village.